Role of selective intralesional embolization in vascular conditions of the nose and paranasal sinuses - Harugop, Anil S.; ., Suhasini; Bellad, Shama; Mulimani, Navin; Sanikop, Adarsh; ., Jahnavi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Preoperative angiographic embolization of major feeding vessels is performed for vascular tumours and has become a valuable, even necessary tool in the surgical treatment of vascular lesions and is likely to improve the results of subsequent surgery. Methods: We have treated six patients, all males, aged between 16-22 years. The patients were informed of the treatment strategy, and their interventions were carried out in accordance with local and general ethical standards and principles. All patients presented with nasal obstruction and epistaxis. Routine blood investigations were done and contrast enhanced CT was done to all patients to know the site of origin, size and extend of the tumour. Five patients were treated with preoperative embolization, whilst one underwent surgery without embolization. Results: The outcome of the surgery in six patients were evaluated and interpreted. Patients who underwent sub selective embolization (SSE) had lowest morbidity and blood loss when compared to the one operated without embolization. Conclusions: Embolization has a vital role to play in many aspects of otolaryngological practice. Using this safe technique of SSE, we achieved a significant shortening of time for surgical removal of the tumour as well as a reduction of total perioperative blood loss.